RELATIONSHIP BETWEEN SELF-REGULATED LEARNING SKILL AND ACHIEVEMENT OF SECONDARY SCHOOL STUDENTS IN PHYSICS IN ENUGU STATE (UNIZIK Journal of STM Education, 2019)
The study focused on the relationship between self-regulated learning skills and achievement scores of physics students in the secondary schools in Enugu state. Three research questions guided the study and three hypotheses were tested at 0.05 level of significance. The study adopted the correlational design. The study population comprised 1,304 SS2 physics students in Enugu Education Zone of Enugu state. A sample of 400 SS 2 physics students obtained using a multi-stage sampling was used in the study. The instrument for data collection was Self-regulated Learning Skills Scale validated by experts. The reliability of the instrument was established using Cronbach Alpha technique which yielded reliability coefficient of 0.73. The method of data collection involved administering the instrument to the students with the aid of research assistants. The data obtained were analysed using Pearson correlation coefficient. The results revealed that a significant low positive relationship existed between self-regulated learning and achievement scores in physics. There is also a significant low positive relationship between male students’ self-regulated learning and their achievement score in physics. However, no significant relationship was found between female students’ self-regulated learning and their achievement scores in physics. The study recommended that orientation exercises should be organized by educational stakeholders for students on the skills of self-regulated learning so as to have greater number of students improve on such skills.
Keywords: Self-regulated learning; physics; achievement; secondary school students